2020
DOI: 10.1021/acs.jafc.9b06386
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Chlorpropham during High-Temperature Processing of Potatoes

Abstract: Chlorpropham is a widely used sprouting inhibitor applied on potatoes during their storage. Currently, severe concerns are raised regarding the potential formation of 3-chloroaniline from chlorpropham during heat treatment. The reactions degrading the molecule in the matrix are quite complex under harsh processing conditions, and a molecular investigation is thus challenging. This study aims to decipher the reaction pathways and to discover new metabolites in typical high-temperature food-processing steps. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Moreover, Gockener et al . found that chlorpropham in potato could be reduced to 27 ± 3% during frying, 36 and could be transferred to frying oil. However, the transfer of pesticides from oil into fried food is still rarely reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gockener et al . found that chlorpropham in potato could be reduced to 27 ± 3% during frying, 36 and could be transferred to frying oil. However, the transfer of pesticides from oil into fried food is still rarely reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the degradation effect of the three pesticides was less than the concentration effect, which could lead to their concentration in peanut oil during frying. 9,[33][34][35] Moreover, Gockener et al found that chlorpropham in potato could be reduced to 27 ± 3% during frying, 36 and could be transferred to frying oil. However, the transfer of pesticides from oil into fried food is still rarely reported.…”
Section: Processing Of Chipsmentioning
confidence: 99%
“…Considering the studies with data on processing below 120 °C (Bai et al, 2021;Bulaid et al, 2005;Chavarri et al, 2005;Duhan et al, 2010;Gockener et al, 2020;Heshmati et al, 2019;Holden et al, 2001;Huan et al, 2015;Jankowska et al, 2019;S. W. Kim et al, 2015;Kontou et al, 2004b;Lin et al, 2005;Łzwicka & Jankwska, 2016;Medina et al, 2021;Meknen et al, 2015;Pallavi et al, 2021;Raveendranath et al, 2014;Sakaliene et al, 2009;Shabeer et al, 2015;Shakoori et al, 2018;Shoeibi et al, 2011;Singh et al, 2017;Soliman, 2001;Walia et al, 2010;Watanabe et al, 2018;Yang et al, 2012;F.…”
Section: Temperatures Below 120 °Cmentioning
confidence: 99%
“…W. Kim et al, 2015;Kontou et al, 2004b;Lin et al, 2005;Łzwicka & Jankwska, 2016;Medina et al, 2021;Meknen et al, 2015;Pallavi et al, 2021;Raveendranath et al, 2014;Sakaliene et al, 2009;Shabeer et al, 2015;Shakoori et al, 2018;Shoeibi et al, 2011;Singh et al, 2017;Soliman, 2001;Walia et al, 2010;Watanabe et al, 2018;Yang et al, 2012;F. Zhao et al, 2020), even though 23 (85%) reported PFs or degradation percent calculations, only three (11%) (Gockener et al, 2020;Kntu et al, 2004b;Lin et al, 2005) investigated the degradation products of the pesticides of interest. Most of the cooking processes were sterilisation, boiling and pasteurisation, even though other processes such as drying, blanching or various cooking processes were also investigated.…”
Section: Temperatures Below 120 °Cmentioning
confidence: 99%
“…Chlorpropham has a low toxicity profile with no acute toxicity effects under (1000 mg/kg/day) after exposure. Long-term exposure to the blood can lead to reduced body weight, decreased hemoglobin and hematocrits and increased blood reticulocyte at high doses (to 1000 mg/kg/day) [4,[7][8][9]. While the effectiveness of CIPC in sprout suppression is highlighted in various studies including [4,5,10], there is a growing concern regarding the safety linked to long term use.…”
Section: Introductionmentioning
confidence: 99%